Beast quest Vedra & Krimon Twin Beasts of Avantia - Blade, Adam (London, Hachette children$1 (Bs group.s, 2008)
Tom and Elenna must protect the twin dragon Beasts, Vedra and Krimon, from the evil Wizard Malvel in this fantasy-adventure special edition.
Keywords: English, Fiction